TECTONIC AND CHRONOSTRATIGRAPHIC IMPLICATIONS OF NEW 40AR/39AR GEOCHRONOLOGY AND GEOCHEMISTRY OF THE ARMAN AND MALTAN-OLA VOLCANIC FIELDS, OKHOTSK-CHUKOTKA VOLCANIC BELT, NORTHEASTERN RUSSIA - Hourigan J.K.; Akinin V.V. (My University, 2004)
The Okhotsk-Chukotka volcanic belt is part of an extensive late Early to Late Cretaceous Andean-style magmatic arc that spans the entire eastern margin of the Asian continent. The belt itself stretches 3000 km from the Chukotka Peninsula to the Uda River and comprises ~ 1.2 x 106 km3 of volcanic rock over a 500,000 km2 area. Despite its size and regional tectonic significance, the time span of magmatic activity is poorly constrained and the subject of significant debate, mostly in the Russian literature. In this paper, we provide new geochronologic control on the timing of inception and cessation of magmatism for the Arman and Maltan-Ola volcanic fields. These field localities were chosen because they are well studied, relatively accessible, and contain floral assemblages that have been used to correlate volcanic sequences at the regional scale. The majority of the volcanic sequence was emplaced between 85.5 ± 1.3 Ma and 74.0 ± 1.2 Ma, as shown by 17 new 40Ar/39Ar ages. The Coniacian– Santonian to Campanian age range indicated is 15 m.y. younger than the Albian to early Cenomanian age range given by a synthesis of floral stratigraphic, K-Ar, and Rb-Sr geochronologic data. The calcalkaline part of the volcanic section spans an apparent age range of 85.5 ± 1.3 Ma to 80.7 ± 0.8 Ma. Capping basalts were emplaced between 77.5 ± 1.1 Ma and 74.0 ± 1.2 Ma and exhibit a within-plate geochemical signature, which we attribute to a temporally and geochemically distinct, possibly extension-related, phase of magmatism. The apparent northwestward migration of the arc front from the interior (seaward) zone (Taigonos Peninsula, Magadan batholith) in Albian–Cenomanian time to the Arman and Maltan-Ola volcanic fields in Coniacian–Santonian to Campanian time may be explained by shallowing of the subducting paleo-Pacific (Kula?) oceanic plate. The flat-lying nature of these volcanic rocks and the within-plate geochemical affinity of the capping basalt unit are inconsistent with prevailing tectonic models for the cessation of arc magmatism and formation of the Sea of Okhotsk which require the collision of a microcontinental block or oceanic plateau with the northeast Asian margin in the Late Cretaceous.
Keywords: Okhotsk-Chukotka volcanic belt; northeast Russia; geochronology; Cretaceous; subduction-related magmatism; Mesozoic::Cretaceous; Мезозой::Меловая